Teacher and student reflections on ICT-rich science inquiry. Issue 1 (2nd January 2017) - Williams, P John; Otrel-Cass, Kathrin
Abstract: Background: Inquiry learning in science provides authentic and relevant contexts in which students can create knowledge to solve problems, make decisions and find solutions to issues in today's world. The use of electronic networks can facilitate this interaction, dialogue and sharing, and adds a new dimension to classroom pedagogy. Purpose: This is a report of teacher and student reflections on some of the tensions, reconciliations and feelings they experienced as they worked together to engage in inquiry learning. The study sought to find out how networked ICT use might offer new and different ways for students to engage with, explore and communicate science ideas within inquiry. Sample: This project developed case studies with 6 science teachers of year 9 and 10 students, with an average age of 13 and 14 years in three New Zealand high schools. Teacher participants in the project had varying levels of understanding and experience with inquiry learning in science. Teacher knowledge and experience with ICT were equally diverse. Design and Methods: Teachers and researchers developed initially in a joint workshop a shared understanding of inquiry, and how this could be enacted. During implementation, the researchers observed the inquiry projects in the classrooms and then, together with the teachers, reviewed and analysed the data that had been collected. Results: At the beginning of the project, some of the teachers and students were tentative: inquiry based teaching supported by ICT meant initially that the teachers were hesitant in letting go some of the control they felt they had over students learning, and the students felt insecure in adopting some responsibility for their own learning. Over time a sense of trust and ease developed and this 'control of learning' balance moved from what was traditionally accepted, but not without modifications and reservations. Conclusions: There is no clear pathway to follow in moving towards ICT-supported science inquiry in secondary schools. The experience of the teacher, the funds of knowledge the students bring to the classroom, the level of technological availability in the school and the ability of the students are all variables which determine the nature of the experience.